Effects of post-exercise stretching versus no stretching on lower limb muscle recovery and performance: a meta-analysis - Zhang, Pei; Chen, Jiangzhou; Xing, Taofeng (Frontiers in Physiology, 2025)
BackgroundPost-exercise stretching is widely employed in athletic and rehabilitation settings to promote recovery and performance. However, its physiological benefits remain controversial due to inconsistent findings across randomized controlled trials.ObjectiveTo evaluate the effects of post-exercise stretching compared to no stretching on lower limb muscle recovery and performance indicators, including muscle soreness, strength, flexibility, performance, and pain threshold.MethodsA systematic search was conducted in eight databases up to 20 July 2025. Randomized controlled trials, controlled clinical trials, and crossover trials comparing post-exercise stretching (static, dynamic, or PNF) with no stretching were included. Data were synthesized using random-effects models, and effect sizes were expressed as standardized mean differences (SMDs). Risk of bias was assessed using the Cochrane RoB 2.0 tool.ResultsFifteen studies (n = 465 participants) were included. Post-exercise stretching showed and statistically non-significant effects on muscle soreness (SMD = −0.06, 95% CI: [−0.32, 0.19], p = 0.63), strength (SMD = 0.27, 95% CI: [−0.14, 0.68], p = 0.19), performance (SMD = 0.18, 95% CI: [−0.11, 0.46], p = 0.22), flexibility (SMD = −0.06, 95% CI: [−0.31, 0.20], p = 0.67), and pain threshold (SMD = −0.02, 95% CI: [−0.41, 0.37], p = 0.93). Sensitivity analysis and Egger’s test indicated robust results and no publication bias.ConclusionPost-exercise stretching, when used as a standalone recovery intervention, does not significantly improve soreness, strength, performance, flexibility, or pain threshold. While physiologically safe and practical, its effectiveness may be limited, warranting integration with multimodal recovery strategies in future applications.Systematic Review RegistrationIdentifier CRD420251113484.